INNOVATIVE APPROACH IN THE DEVELOPMENT OF THE KAZAKHSTAN ECONOMY - Zh.B. Khamidullina; A.K. Ermekbaeva; S.B. Zhubanova (Academic Journal of Physical and Chemical Sciences, 2019)
According to the research, an innovative approach to the development of the Kazakhstan economy has very significant differences in the activity of economic entities, and this primarily depends not only on regional affiliation due to the heterogeneity of the innovation infrastructure of the regions, but also on the differences in the availability of scientific and technical, financial, labor and other resources. At the same time, the state of innovation activity is the most important indicator of the development of society and the economy in any state. However, in developed countries, innovation is an integral part of the state socio-economic policy, which is indicative of Kazakhstan, given the relevance and importance of innovation for socio-economic development, the issues of enhancing innovation are identified, according to the authors, as the most important priorities of the country's economic development.